Analisis Fenomenologi dan Psikososial Tokoh Utama dalam L’Enfance d’un Chef Karya Sartre - Hariyani Susanti, R.; Aramudin, Aramudin (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
This research aims to apply the phenomenological and psychosocial approaches in analyzing the main character in "L’Enfance d’un Chef" by Jean-Paul Sartre. In this study, the author uses a qualitative descriptive method to explore the subjective experience of the character and the concept of freedom in the literary work. This research contributes to a deeper understanding of human experience in their social environment through a phenomenological approach in literature. The study starts with identifying the background and context of the literary work and exploring the theories related to this research, including phenomenology and psychosocial theory. The author applies phenomenological and psychosocial approaches to analyze the main character and understand his subjective experience. The results show that the main character, Lucien, has a complex and interrelated subjective experience with his social environment. Phenomenological analysis helps the author understand how Lucien perceives and gives meaning to his life experience, while psychosocial analysis helps the author understand the social and psychological factors that influence Lucien's life experience. The conclusion of this study is that the phenomenological and psychosocial approaches can be used to analyze characters in literature and can provide a deeper understanding of the subjective experience of humans in their social environment